Analisis Yuridis terhadap Kedudukan Anak Hasil Perkawinan Siri - Bella Yulfarida (Universitas Sebelas Maret, 2021)
The purpose of this study is to determine the juridical analysis of the position of the child, the legal status of the child and to find out the government's efforts to overcome the position of the child from an unregistered marriage. This type of research is an empirical descriptive qualitative. The data source uses primary data sources and secondary data sources. Data collection techniques are interviews, observation and documentation. The results of the study indicate that children resulting from unregistered marriages are registered and then registered in the civil registration in order to obtain a legal legal position. The legal status of unmarried children is that after the Decision of the Constitutional Court Number 46/PUU-VIII/2010, if it can be proven based on science and technology and/or other evidence, it turns out that they are related by blood as their father, then they are entitled to inherit from their father. The government's effort in overcoming the position of children from unregistered marriages is to socialize so that siri couples become legal marriages, namely by registering with marriage istbat and re-marrying.Keywords: legal status, legal status, children, unregistered marriage